(3NWHI YGFTI QVi Gddg YfgG aj CHjgG hJaSjQ ZQjHgG hdZJgGs - (3CHh HcQ eMeO Hf GdbGSe Hf HTGQ Hf GdCfHGQis; (3GHf GdGfHGQj , CHh HcQ eMeO Hf GdbGSe Hf eMeO Hf HTGQ Hf GdMSjf GdCfHGQj, CHh HcQ GdCfHGQj,J (B328 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3CNHQfG TjNfG GdMGaX Rci GdOjf YHO GdYXje GdefPQi HdZ YGFTI QVi Gddg YfgG Cf bhekG jfGdhf ef CHjgG QVi Gddg Yfg , aCQSdJ Edi CQadI ef GdfGS s
(3BNQgG (B:s
(3JeJ NWHI YGFTI QVi Gddg YfgG hJaSjQ ZQjHgG hdZJgG hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3cJHJ GdeLehYI HQSe NRGfI GdebQ GdCTQa GdYGdi Gdehdhi GdCejQ GdSjai SfI (B673(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B334 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B143s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs